FEATURES OF UNIVERSAL ELEMENTS OF CORPORATE CULTURE DEMONSTRATION IN DIFFERENT COUNTRIES: THE QUESTION OF COMPANY’S CORE VALUES AND INTERCULTURAL INTERACTION - Mingaleva, Zhanna; Deputatova, Ludmila (PEOPLE: International Journal of Social Sciences, 2018)
An analysis of the company’s core values and their relationship to the national culture of employees is presented in the article. The management of the international working group requires special approaches to the management of personnel, in terms of the formation and translation of adequate values to the team. Questioning of workers of different nationalities of international companies operating in Russia was used as the main research method. In the process of questioning, the opinions of workers of different nationalities about the presence in their companies of the main elements of the organizational culture were revealed and an assessment of these elements was made. It was concluded that the elements of the company’s organizational culture are correlated with the national values of employees. Zones for improving the corporate spirit, contributing to the disclosure of the creative and communicative potential of the working group were identified in the study. The main elements of the non-national (global) organizational culture are also highlighted in the article. It is: the culture of lifelong learning, the culture of leadership, collectivism, solidarity of workers in the performance of a single task, attitude to failure. The key values of the company were: development, initiative, team, honesty, trust.